Teaching With Purpose : Closing the Research-Practice Gap. - Penick, John (National Science Teachers Association (NSTA), 2005)
Teaching with Purpose provides a framework for coordinating your unique students and school with your desired educational outcomes and the education research literature. You can use this framework in several aspects of teaching: for planning lessons and units, selecting activities and curriculum, and analyzing your role as teacher. All this is explained within the books easy-to-grasp structure. It covers the case for a research-based teaching rationale, the elements of such a rationale, how to develop and implement it, and then how to become a mentor to others.